River water quality modelling in developing a catchment water safety plan - Vieira, J. M. Pereira (2014)
The primary aim of a catchment water safety plan is to reduce risks within the catchment to protect the quality of drinking water sources at the intake point. Even where effective arrangements for catchment management and control have been implemented, unexpected deterioration in raw water quality can pose a risk to treated drinking water quality. Thus potential sources of pollution impacting the area of influence of the intake should be identified and monitored. An important part of any catchment management strategy includes implementation of raw water monitoring programmes, targeted at the most likely microbiological threats to water treatment. When combined with good monitoring datasets, properly calibrated, tested and verified surface water models can be used to forecast or estimate risks under various scenarios. This allows a good insight into impacts associated with known and anticipated land use activities within the catchment. In this work a hybrid methodology based on river water quality data analysis and hydrodynamic and water quality modelling was developed to assess the surface water quality in the Portuguese river Cávado. This component constitutes the base for developing a catchment water safety plan at this river basin.